Inventarisasi dan Identifikasi Karakteristik Sub DAS di Wilayah Hutan Lindung Register 20 Pesawaran - Suprapto Suprapto (Jurnal Ilmiah Teknik Pertanian - TekTan, 2015)
Characteristics of sub-watershed is a specific description of the sub-watershedÂ  characterized by parameters related to morphometry, topography, soils, geology, vegetation, land use, hydrology and human. The objectives of this research are to obtain data on the characteristics of sub-watershed in the area of Forest Protected Areas Register 20 Pesawaran District, and estimate conditions, potential, and behavior/character necessary for the development of natural resources and human resources as well as institutional optimal. The research was done by identification of morphological criteria and morphometric mengidentikasi subzone, as well as the parameters subzone which is a very important element in relation to the response of rain falling in the sub-watershed into a run-off. The identification results show that the shape subzone is dominated by an elongated shape, orientation (aspect) sub-watershed is dominated by northwest direction, slope (slope) sub-watershed is dominated by the slope is steep and a bit steep, the flow pattern (drainage pattern) dominated the flow pattern denditrik, density dominated rivers grade medium density, land use is dominated by a mixture of dry land agriculture, as well as socio-economic characteristics are dominated by the rural economy.Â Keywords: characteristics of sub-watershed, forest protected areas register 20 pesawaran district